2021
DOI: 10.1097/jsm.0000000000000955
|View full text |Cite
|
Sign up to set email alerts
|

Visio-Vestibular Deficits in Healthy Child and Adolescent Athletes

Abstract: Objective: To determine the relationship between patient characteristics and performance on the visio-vestibular examination (VVE) in a cohort of healthy youth athletes and explore the potential association between the VVE and other standardized concussion batteries. Design: Cross-sectional. Setting: Suburban middle and high school. Patients: One hundred ninety subjects age 11 to 18 enrolled before their respective scholastic sport season between August 2017 and March 2020. Assessment of Independent Variables:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Conditions affecting the vestibular-visual system simulate ADHD symptoms and can be assessed with vestibular, visual, and audiologic testing and referral to suitable specialists (ie, audiologist, ophthalmologist, or otorhinolaryngologist). 38,39…”
Section: Results/literature Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Conditions affecting the vestibular-visual system simulate ADHD symptoms and can be assessed with vestibular, visual, and audiologic testing and referral to suitable specialists (ie, audiologist, ophthalmologist, or otorhinolaryngologist). 38,39…”
Section: Results/literature Summarymentioning
confidence: 99%
“…36,37 Conditions affecting the vestibular-visual system simulate ADHD symptoms and can be assessed with vestibular, visual, and audiologic testing and referral to suitable specialists (ie, audiologist, ophthalmologist, or otorhinolaryngologist). 38,39 It has also been reported that psychosocial factors, such as social media, can lead to impaired attention, memory, information processing, and problem-solving (Table 6). 40,41 Effects of stress or considerable fluctuations in the athlete's environment, including school absence, disorientation, and changes in mental health, can mimic ADHD.…”
Section: Adhd Mimics: Pattern Identification For Differentiationmentioning
confidence: 99%
“…Finally, we used Fisher exact test to compare the proportion of participants for whom recovery based on symptom score could be elucidated. We defined recovery in the EMA group as total PCSI symptom score ≤ 5 at any point during the 21-day follow-up, based on normative data in both national and local samples 22,23 . Given a lack of consistency in follow-up clinical documentation of standardized symptom scales, we defined recovery at follow-up clinical visits as complete symptom resolution.…”
Section: Methodsmentioning
confidence: 99%
“…We defined recovery in the EMA group as total PCSI symptom score ≤ 5 at any point during the 21-day follow-up, based on normative data in both national and local samples. 22,23 Given a lack of consistency in follow-up clinical documentation of standardized symptom scales, we defined recovery at follow-up clinical visits as complete symptom resolution. We conducted analyses using Stata version 14.2 (College Station, Tex).…”
Section: Statistical and Power Analysismentioning
confidence: 99%
“…Finally, we compared the total PCSI/cPCSI symptom score to predetermined thresholds normalized for age and sex based on data for uninjured youth (PCSI <9 for women, PCSI <6 for men, and cPCSI <10 for both sexes). 10 These participants were categorized as recovered as defined by symptoms below standardized threshold (8).…”
Section: Symptom-based Recoverymentioning
confidence: 99%